EFEKTIFITAS PEMBERIAN ASI EKSLUSIF TERHADAP PERTUMBUHAN DAN PERKEMBANGAN BAYI DI POSYANDU MAWAR KECAMATAN MERSI TAHUN 2015 - Dewi, Feti Kumala (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2016)
ABSTRACT : EFECTIVITENESS OF EXCLUISVE BREAST FEEDING BABY ON THE GROWTH AND DEVELOPMENT IN POSYANDU MWAR DISTRICT OF MERSI 2015. Factors affecting infant growth inhibition one low parental nutrition to children. Nutritional needs for infants starting from breastfeeding exclusively. Stimulation Detection and Early Intervention Growth (SDIDTK) is an activity or investigation to find any irregularities early growth and development in infants and preschool children. Purwokerto Timur is a region with a live birth rate reached 678 babies in 2013. While in 2014, the live birth rate reached 754 exclusively breastfed infants with coverage reaching 54.88%. Objective: To determine effectiveness of exclusive breastfeeding on Growth and Development of Infants in Posyandu Mawar District of Mersi Year 2015 Type of research: analytic correlational, using the Kolmogorov Smirnov test data analysis. Total population of 27 infants, then the sampling is done by purposive sampling 27 samples. Instruments in this study using questionnaires KPSP, TDD, BB / TB, LK.Results: Breastfeeding Exclusive effective on Growth (Round Head) Baby, but granting exclusive breastfeeding is less effective on growth (weight/height), Development (KPSP), development (Test Power Listen/TDD) Baby in Posyandu Mawar District of Mersi 2015. Â Keywords: exclusive breastfeeding, baby, Growth and Development